Translation and Migration, Utopia and Dystopia: Representations of the Labor of Cultural Mediation in Fictional Eastern Europe and the Real US-Mexico Border - James L Richie IV (Vernacular: New Connections in Language, Literature, & Culture, 2025)
With the publication of Moira Inghilleri’s book, Translation and Migration (2017), the linguistic act of translation and the social phenomenon of migration have been linked in the world of interdisciplinary studies, yet this linkage may obscure the relevance of works in which only one phenomenon (translation or migration) is presented. A case study in which a work exploring migration can be contrasted with a work exploring the function of translation may reveal in one another the social forces that condition both practices. In Lucas Pope’s independently created video game Papers Please (2014), the player embodies a border patrol agent in a fictional country reminiscent of the Eastern Bloc; In Valeria Luiselli’s autobiographical work Tell Me How It Ends: An Essay in Forty Questions (2017), Luiselli recounts her experience as an interpreter conducting interviews with child asylum-seeking migrants. While these works may seem, at a glance, to be unrelated, in reality, they show the experiences in the migration process which have been thought to be the contradictions of one another: that of the interpreter and that of the customs official. By highlighting the subjective experience of both agents in this process, the two works can illuminate the multi-dimensional aspects of translation and migration. Moreover, current research in anthropology, philosophy, and translation theory can connect these dual experiences to theory which reflects the greater social forces that drive immigration and its violent response. Analyzing works which lead audiences to experience the labor of cultural mediation for themselves can reveal means by which the popular perception of translator figures, and by extension the foreign, could be ameliorated in an aggressively monolingual society.
Keywords: David Graeber; Soviet Union; Translation Theory; Video Games; US Latinx Literature